2022
DOI: 10.21203/rs.3.rs-1927825/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Gherlin and Leptin Hormones in Patients with Major Depressive Disorder

Abstract: The effects of vitamin D supplementation on the levels of leptin and ghrelin hormones were evaluated in patients diagnosed with major depressive disorder (MDD). 72 participants were recruited in this study (40 MDD patients and 32 healthy controls (28 males & 44 females). Blood samples were collected at the beginning of the study to determine the baseline values of different biochemical tests including vitamin D, leptin, and ghrelin hormones. Participants were treated weekly, under physician supervision, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Intriguingly, the subgroup analysis of gender demonstrated that vitamin D supplements significantly alleviated depression scores in all females, regardless of whether they were depressed or not. A previous study (68) found that female patients with depressive symptoms improved significantly more following vitamin D administration than male patients, which was in accordance with our findings. The mechanism might involve that vitamin D has a bearing on the synthesis of serotonin and a moderate amount of vitamin D may elevate the level of extracellular serotonin (69), particularly in females, so as to improve the symptoms of depressive disorder.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, the subgroup analysis of gender demonstrated that vitamin D supplements significantly alleviated depression scores in all females, regardless of whether they were depressed or not. A previous study (68) found that female patients with depressive symptoms improved significantly more following vitamin D administration than male patients, which was in accordance with our findings. The mechanism might involve that vitamin D has a bearing on the synthesis of serotonin and a moderate amount of vitamin D may elevate the level of extracellular serotonin (69), particularly in females, so as to improve the symptoms of depressive disorder.…”
Section: Discussionsupporting
confidence: 93%